Risk Disclosure in IPO Prospectuses: A Descriptive Study in the Indonesian Capital Market - Meidiaswati, Harlina; Dwi Kusumawati , Nunik; Sasikirono, Nugroho; Faiz Akbar, Rasyidi (Proceeding of International Management Conference and Progressive Papers, 2024)
This study aims to describe risk disclosure in the IPO prospectuses of companies listed on the Indonesia Stock Exchange during the 2021-2023 period. Using a quantitative approach with a descriptive design, this study analyzes four risk categories: primary risk, business risk, general risk, and investor risk. Data were collected using a documentation technique using purposive sampling, covering 176 companies that published complete information in their prospectuses. The results show that principal risk disclosure is the lowest, while general risk disclosure is the highest. Variation in risk disclosure between companies, as measured by standard deviation, indicates that general risk is the most heterogeneous, while investor risk is the most homogeneous, indicating consistency in disclosure between companies. These findings indicate an imbalance in the depth of information, particularly related to principal and general risks. Based on signaling theory, it is recommended that IPO companies improve the transparency of risk disclosure to provide more complete information to investors. Future research can explore the relationship between risk disclosure and IPO stock performance..